The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/adt.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Problems With Executive Dysfunction and Impulsivity in Adults Recovering From Methamphetamine Addiction

Abstract: Objectives Compared with non-addicted controls (CTLs), adults in remission from methamphetamine addiction (MA-REM) evidence impairments on objective measures of executive functioning and impulsivity. Methods To evaluate the impact of these impairments in MA-REM adults, demographically matched groups (MA-REM, n=30; CTLs, n=24) completed objective and self-report measures of executive functioning and impulsivity. Results MA-REM adults demonstrated significantly (p < 0.050) greater objective and subjective pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
(35 reference statements)
2
7
0
2
Order By: Relevance
“…QOL, the perception of one's position in life, comprises physical (energy, pain, and difficulties engaging with activities of daily living and work), psychological (affect, self‐perception, perceived cognition), social (personal relationships, social and sexual activity) and environmental (financial/accommodation stability and access to services/information) domains . Previous research has identified that MD is associated with poorer QOL in at least three of these domains: physical (physical and medical impairment ), psychological (diminished emotional control , high rates of anxiety, depression and psychosis ) and social (high interpersonal conflict and lower social support ). Improvement in such domains is a key focus for treatment, with QOL and wellbeing identified as key indicators of addiction recovery and treatment success .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QOL, the perception of one's position in life, comprises physical (energy, pain, and difficulties engaging with activities of daily living and work), psychological (affect, self‐perception, perceived cognition), social (personal relationships, social and sexual activity) and environmental (financial/accommodation stability and access to services/information) domains . Previous research has identified that MD is associated with poorer QOL in at least three of these domains: physical (physical and medical impairment ), psychological (diminished emotional control , high rates of anxiety, depression and psychosis ) and social (high interpersonal conflict and lower social support ). Improvement in such domains is a key focus for treatment, with QOL and wellbeing identified as key indicators of addiction recovery and treatment success .…”
Section: Introductionmentioning
confidence: 99%
“…In social settings, impulsive action is significantly predictive of language difficulties and problems with planning recreational activities . Psychological aspects of QOL are also impacted; diminished emotional self‐control has been observed in MD individuals with heightened impulsive choice and action . Impulsive action is also associated with deficits in managing transportation and finances , medication management, completing chores around the home and reduced activities of daily living performance .…”
Section: Introductionmentioning
confidence: 99%
“…Both impulsivity and working memory are individually predictive of substance use and are consistently impaired in individuals with MUD (Ellis et al 2016;Zhong et al 2016). There is a strong theoretical rationale for the link between impulsivity, working memory and drug use in individuals with MUD; however, past research has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study supports this finding, as not only were treatment-seeking MA dependent individuals less behaviorally inhibited on objective measures of impulsivity, but they also had higher levels of subjective impulsivity relative to controls (Ellis, et al, 2016). A common measure used to assess subjective impulsivity is the Barratt Impulsiveness Scale (BIS-11), which has been divided into three second-order factors, including Attentional, Motor, and Non-planning impulsiveness (Patton, Stanford, & Barratt, 1995).…”
Section: Introductionmentioning
confidence: 70%
“…First use of MA occurs at about 22 years of age (Center for Behavioral Health: Statistics and Quality, 2015), during the transition between late adolescence and emerging adulthood. While many factors may be associated with the initiation and maintenance of MA use, impulsivity is a personality trait found to be higher in MA users relative to healthy controls (Ballard, et al, 2015; Ellis, et al, 2016; Hoffman, et al, 2006). …”
Section: Introductionmentioning
confidence: 99%